Patterns of triggers for on-task and off-task behaviors: university students in independent study - Liu, Yan; Deng, Lisa; Lin, Lin; Gu, Xiaoqing (Interactive learning environments, 2023)
With the rapid development of mobile devices and web-based technologies, it becomes common for students to switch between different tasks during study time. However, it remains unclear how the transition between on-task and off-task states happens and how digital devices affect the process. This study examines college students' independent study in the library to delineate the pattern of on-task and off-task behavior, and identify the triggers for students' engagement or disengagement. Through video recordings, the researchers captured the behaviors of over 266 students at the library. Observations were taken and used to double-check and confirm the behaviors. The study adopted the behavioral sequences method to scrutinize behavioral transition and explored gender differences. The results indicate that on-task behaviors tended to decline as the learning duration increased, whereas off-task behaviors tended to increase when students interacted with personal devices. As the most used device, smartphones posed persistent interference for learners, leading to reduced focus during independent study time. Moreover, male students were more likely to be influenced by external interruptions, whereas female students were more prone to the influence of internal interruptions. These findings can contribute to the development of research-based guidelines for improving students' attention and self-adjusting during self-study time.